Chrysophanol suppresses pro-inflammatory response in microglia via regulation of Drp1-dependent mitochondrial fission. (3rd September 2017) - Chae, Unbin; Min, Ju-Sik; Lee, Hanna; Song, Kyung-Sik; Lee, Hyun-Shik; Lee, Hong Jun; Lee, Sang-Rae; Lee, Dong-Seok
Abstract: Objectives: Chrysophanol, also called chrysophanic acid, is a natural anthraquinone compound found in Rheum palmatum. R. palmatum has been used in oriental medicine in ancient East Asia. Microglial cells represent not only the forefront immune defense in the central nervous system but also the most reactive sensors to various threats. However, activated microglia can exert neurotoxic effects via excessive production of cytotoxic molecules and proinflammatory cytokines. Therefore, modulation of microglial cell activation is important for maintaining neuronal function. Materials and methods: Pretreatment of chrysophanol in BV-2 murein microglial cells was carried out for 1 hour, followed by stimulation with 1 μg/mL LPS. Level of proteins and RNAs were detected by western blotting and Reverse Transcriptase PCR. DsRed2-Mito-expressing cells were used for detecting mitochondrial morphology. Results: In this study, we determined the effects of chrysophanol on lipopolysaccharide (LPS)-induced microglial activation. Chrysophanol inhibited the LPS-induced production of proinflammatory mediators and cytokines via suppression of mitogen-activated protein kinase/nuclear factor kappa-B activation and reactive oxygen species generation. In addition, chrysophanol downregulated LPS-induced mitochondrial fission by diminishing dynamin-related protein 1 (Drp1) dephosphorylation. Taken together, chrysophanol suppressed the proinflammatory response of activated microglia via inhibition of Drp1-dependent mitochondrial fission. Conclusion: Our findings can provide the basis for the use of chrysophanol in microglial inflammatory response-mediated neurodegenerative diseases. Furthermore, our study can contribute to the production of new drugs for inflammatory response-mediated neurodegenerative diseases by purification of chrysophanol.